PROBLEMATIKA NIKAH SIRI DAN AKIBAT HUKUMNYA BAGI PEREMPUAN - Syukri Fathudin Ahmad Widodo; Vita Fitria (Jurnal Penelitian Humaniora, 2010)
This is a qualitative research which is aimed at obtaining the deeper comprehension on phenomenon of nikah siri. Although religiously legal, nikah siri , in fact, raises many problems which cause losses to the women party. Nikah siri is usually taken as a shortcut of man-woman relationship legalization, which basically is a breaking on The Law of Marriage, no 1, 1974, particularly on its record. By using SWOT gender analysis, the result shows that the background motives of wedding contract were relatively various. Nevertheless in general, they did it for a reason of religious legality. With deep interviews, the researchers succeeded to reveal the respondents’ problems within their marriage. The main problems suffered by woman respondents were psychological. They got stressed as the result of the uncertainty of their marriage law status. Witnessing the disadvantages, it is important to reconsider the legality of contract wedding which is commonly used as a legalization of man-women relationship